Information science in theory and practice - Vickery, B. C. (Brian Campbell) (Gale virtual reference library, 2004)
"An introduction to the field of information science text that covers the most recent changes to affect the profession, including the Internet and its role in information science and librarianship. Of academic and professional interest."--GVRL description.